(untitled) (Research, Society and Development, 2024)
The clinical signs of neonatal cholestasis such as jaundice, acholia, choluria are easily noticeable. However, it is up to the pediatrician to quickly differentiate the cause of cholestatic hyperbilirubinemia due to the pediatric emergency situation whose late diagnosis can be potentially serious and lethal. This study aimed to identify the main causes of cholestatic jaundice in newborns and infants and how pediatricians can carry out an early diagnostic approach and initiate treatment. As this is an integrative review article, it proposes to practically assist in addressing the main differential diagnoses of cholestatic jaundice and available therapies. The bibliographic bases searched: Cocrhane, Embase, Medline and Pubmed. The selection criteria: free articles in full between 2019 and 2024, in Portuguese, English or Spanish, and the presence of at least two of the descriptors. Therefore, in the case of a jaundiced newborn over two weeks old, the pediatrician must request a bilirubin measurement, as cholestasis is always pathological with direct values greater than 1.0 mg/dl and the causes can be extra or intrahepatic with a challenging picture of differential diagnoses. In the extra hepatic we have biliary atresia whose early surgical approach leads to a more favorable prognosis. Therefore, when investigating neonatal cholestasis, the pediatrician needs to start from the most common diseases, prioritizing those with surgical treatment due to the risk of mortality. It is essential to the investigation to carry out anamnesis of the mother-infant binomial, detailed physical examination, evaluation of the characteristics of the feces, laboratory and imaging tests, if necessary, biopsy with histopathology and referral to a specialist.